Pathogenic Variants in MT-ATP6: A United Kingdom-Based Mitochondrial Disease Cohort Study - Yi Shiau Ng; Mika H. Martikainen; Gráinne S. Gorman; Alasdair Blain; Enrico Bugiardini; Apphia Bunting; Andrew M. Schaefer; Charlotte L. Alston; Emma L. Blakely; Sunil Sharma; Imelda Hughes; Albert Lim; et al. (WILEY, 2022)
Distinct clinical syndromes have been associated with pathogenic MT-ATP6 variants. In this cohort study, we identified 125 individuals (60 families) including 88 clinically affected individuals and 37 asymptomatic carriers. Thirty-one individuals presented with Leigh syndrome and 7 with neuropathy ataxia retinitis pigmentosa. The remaining 50 patients presented with variable nonsyndromic features including ataxia, neuropathy, and learning disability. We confirmed maternal inheritance in 39 families and demonstrated that tissue segregation patterns and phenotypic threshold are variant dependent. Our findings suggest that MT-ATP6-related mitochondrial DNA disease is best conceptualized as a mitochondrial disease spectrum disorder and should be routinely included in genetic ataxia and neuropathy gene panels. ANN NEUROL 2019;86:310-315